An analysis of the reach and effectiveness of distance learning in India during school closures due to COVID-19. (September 2021) - van Cappelle, Frank; Chopra, Vidur; Ackers, Jim; Gochyyev, Perman
Highlights: Beyond an access digital divide is a divide in effective use of learning technology. Radio and TV are underutilized as learning modalities for adolescents in India. Teacher contact and learning modalities are associated with perceived learning. Female adolescents perceive their learning to be significantly less. Equity issues in opportunities for effective use of devices need to be addressed. Abstract: In India, more than 276 million children and youth were out of school for extended periods since March 2020 due to school closures in response to COVID-19. A key challenge has been how to measure the impact of responses to continuity of learning both to ensure more effective responses in the event of further disruptions, but also to help the education community conceptualize more creative and effective approaches to learning, through blended and flexible approaches. This study reflects on the findings from a UNICEF survey targeting parents and adolescents across 6 states in India, and identifies lessons learned for addressing learning inequities during future school closures. We focus on measuring three key variables – access to technology, their utilization, and perceived learning for different profiles of children. As students began learning from home, technology access rates in households were initially used to determine the estimated maximum reach of different distance learning modalities during school closures. Beyond access, we find significant variations in adolescents' use of technology for learning purposes and their perceptions of learning, linked to the type of remote learning modality, gender, location and type of school. We discuss the implications for government strategies and policies to ensure better utilization of technologies which are available in households and to address equity gaps in learning opportunities.